2011
DOI: 10.1002/hep.24527
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced liver injury with hypersensitivity features has a better outcome: A single-center experience of 39 children and adolescents

Abstract: Drug-induced liver injury (DILI) is rare in children and adolescents, and, consequently, data are remarkably limited. We analyzed the causes, clinical and biochemical features, natural history, and outcomes of children with DILI. Consecutive children with DILI from 1997 to 2004 (retrospective) and 2005 to 2010 (prospective) were studied based on standard criteria for DILI. Thirty-nine children constituted 8.7% of 450 cases of DILI. There were 22 boys and 17 girls. Median age was 16 years (range, 2.6-17). Combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 46 publications
2
70
2
Order By: Relevance
“…Features of immunoallergic or hypersensitivity reactions are observed more commonly in children, with 41% of 39 children in one study demonstrating immunoallergic features. 16 Presence of hypersensitivity features is often associated with good prognosis 16 ; a similar observation was made by the Spanish DILI group in whom this reaction was seen in 23% of their 461patients. 18 An indirect evidence for a better outcome was provided by Bjornsson et al who observed eosinophilia including liver eosinophilia in their patients.…”
Section: Pathogenesis Of Drug-induced Hepatitismentioning
confidence: 59%
See 4 more Smart Citations
“…Features of immunoallergic or hypersensitivity reactions are observed more commonly in children, with 41% of 39 children in one study demonstrating immunoallergic features. 16 Presence of hypersensitivity features is often associated with good prognosis 16 ; a similar observation was made by the Spanish DILI group in whom this reaction was seen in 23% of their 461patients. 18 An indirect evidence for a better outcome was provided by Bjornsson et al who observed eosinophilia including liver eosinophilia in their patients.…”
Section: Pathogenesis Of Drug-induced Hepatitismentioning
confidence: 59%
“…9 Patients presenting with hypersensitivity DILI have a milder disease and a better survival, particularly in children. 16,18 Hypersensitivity DILI is often accompanied by immunoallergic features such as skin rashes, eosinophilia or lymphadenopathy. These characteristics may aid in the differentiation of hypersensitivity DILI from the metabolic idiosyncrasy variety (Table 3).…”
Section: Presentation and Severity Of Drug-induced Liver Injurymentioning
confidence: 99%
See 3 more Smart Citations